2003
DOI: 10.1373/49.9.1450
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Multiple Reverse Transcription-PCR Tyrosinase Testing for Circulating Neoplastic Cells in Malignant Melanoma

Abstract: Background: The reverse transcription-PCR tyrosinase assay (TYR test) cannot reliably detect malignant melanoma (MM) cells in blood as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 37 publications
(30 reference statements)
1
19
0
5
Order By: Relevance
“…More importantly, detection of CMCs was shown to be an indicator of early relapse and poor survival from melanoma [64,[66][67][68][70][71][72]74]. Multiple tests were shown to increase the sensitivity of detection of CMCs [ [75][76][77] and tests carried out up to 6 months after surgical removal of localized melanoma were still shown to be associated with an adverse prognosis [70]. Curry et al [75] found that tests on three blood samples taken in the first 3 months after surgical removal of melanoma provided the highest sensitivity for detection of CMCs.…”
Section: Staging Using Markers In the Blood Circulating Melanoma Cellsmentioning
confidence: 99%
“…More importantly, detection of CMCs was shown to be an indicator of early relapse and poor survival from melanoma [64,[66][67][68][70][71][72]74]. Multiple tests were shown to increase the sensitivity of detection of CMCs [ [75][76][77] and tests carried out up to 6 months after surgical removal of localized melanoma were still shown to be associated with an adverse prognosis [70]. Curry et al [75] found that tests on three blood samples taken in the first 3 months after surgical removal of melanoma provided the highest sensitivity for detection of CMCs.…”
Section: Staging Using Markers In the Blood Circulating Melanoma Cellsmentioning
confidence: 99%
“…Previously, Wong et al (11 ) have demonstrated that systemic chemotherapy could apparently remove the CTCs in blood of liver cancer patients. Although systemic chemotherapy, immunotherapy, and chemoimmunotherapy could possibly eradicate the CMCs, Szenajch et al (8 ) did not notice any critical effects of systemic treatment on the persistence of CMCs in melanoma patients. Apparently, multiple TYR mRNA diagnostic testing can be useful for molecular cancer staging for melanoma patients and hence for prediction of relapse or development of metastases.…”
mentioning
confidence: 96%
“…The frequency of TYR mRNA positivity during repeated testing was significantly associated with melanoma stage, recurrence, and overall survival (8 ). Although a single positive TYR test could indicate the risk of relapse, multiple RNA diagnostic testing on multiple blood samples may predict cancer progression more accurately.…”
mentioning
confidence: 99%
See 2 more Smart Citations